THE CONTRIBUTION OF LIBERAL EDUCATION IN THE SUCCESSFUL PERSON`S TRAINING IN THE UNITED STATES (ON THE EXAMPLE OF THE ENGLISH MAJOR) - Kozmenko, Olena (Educological discourse, 2020)
The article is devoted to the examine of the role of liberal education in general, and the English major in particular in the process of training a successful person in US higher education. Liberal Arts colleges have been training students in the country since colonial times and have always been characterized by high quality education. These colleges were charged with providing a broad-based education that would prepare students for a wide variety of professions. With the beginning of a new era, in the twentieth century, Americans' priorities changed and it was a devaluing of the humanities in favor of science, technology, engineering, and mathematics (STEM) and applied programs designed to prepare graduates for specific jobs and careers. However, understanding the importance of the humanities in the process of formation of decent American citizens and successful individuals encourages colleges and universities to look for ways to improve the effectiveness of liberal arts education, renew the educational process, and increase the competitiveness of the humanities in the U.S. labor market. English major provides unique opportunities for the formation of skills that are vital to a successful life. The efforts of higher education establishments to improve the situation with philological education and attract new students is analyzed in the article. The content of the educational program is considered, the data of scientists on its updating, examples of concrete innovations are given. The important role of English language and literature in preparing students for success after graduation, career prospects is confirmed by numerous American scientists` studies. The article presents the work of educators who prove the importance of liberal education in the formation of intellectual and moral qualities of the individual, tolerant attitude towards other people and cultures, critical thinking skills, productive communication, collaboration as well as active citizenship. Also in the article it is considered the relevance of the English major in modern world and career prospects for specialists in English philology.